KAJIAN HERMENEUTIKA DALAM KITAB Al-SUNNAH Al-NABAWIYYAH KARYA MUHAMMAD AL-GHAZALI: ANALISIS HADIS TENTANG NYANYIAN: Analisis Hadist tentang Nyanyian - Ihsan Nurmansyah Ihsan Nurmansyah (Al Irfani: Journal of Al Qur'anic and Tafsir, 2021)
Muhammad al-Ghazali is a figure who is quite controversial with his work al-Sunnah al-Nabawiyyah baina Ahl al-Fiqh wa Ahl al-Hadith, where there are those who give a positive appreciation of the hermeneutics of hadith he offers, but there are also those who accuse him of being incar al-Sunnah. Therefore, it is very important to study the hermeneutic thought of Muhammad al-Ghazali's hadith, in this case it is focused on the traditions about singing which are still being debated whether or not it should be done in Islam in the contemporary era. The results of this research can be concluded that the hermeneutics of the hadith of Muhammad al-Ghazali regarding the hadiths regarding singing must be measured from the four criteria of authenticity of the hadiths, namely: 1) the observations of the hadith of the chant do not contradict Al-Qur'an Surah Luqman verse 6; 2) the observance of the singing hadith does not contradict other sahih traditions of the same theme; 3) the observance of the hadith of singing is in accordance with the historical fact that the Prophet praised the melodious voice of Abu Musa al-Asy'ari when reading the al-Qur'an while singing it; 4) the observance of the chanting hadith is in accordance with scientific truth that it can cause different psychological echoes and influences. Singing or listening to songs that have a noble meaning and a good melody is permissible. However, if the poetry and rhythm lead to immorality accompanied by things that are forbidden such as khamr and other heinous acts, then that is not allowed.